PENERAPAN PROGRAM BEHAVIOR BASED SAFETY (BBS) DAN KECELAKAAN KERJA DI PT INALUM KUALA TANJUNG TAHUN 2014 - siti saodah; gerry silaban; arfah mardiana lubis (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Work accidents are mostly caused by unsafe behavior. Behavior Based Safety Program plays an important role to create zero accidents. The implementation of behavior-based safety program is focused to observe the behavior of a process to improve safe work behavior. This study used a descriptive research with cross sectional design approach which aimed to describe the application of behavior-based safety program and work accidents in PT. Inalum Kuala Tanjung year 2013-2014. The samples of this research were all employees which injured in PT.Inalum Kuala Tanjung year 2013 and 2014. The available data were analyzed descriptively. The results showed that the accident happened in 2013 mostly happened in the reduction factory as much as 2 times (40 %) and in 2014 mostly happened in the maintenance as much as 3 times (50%). Work accidents which occurred in 2013 and 2014 mostly caused by unsafe behavior. The application of behavior-based safety program is still new and needs to run a sustainable improvement especially inform improvements of Inalum Secure Card (ISC). The result of the evaluation Inalum Secure Card (IKA) conducted by safety promoter at each department or section each month. But not all safety promoter reported the result of the evaluation Inalum Secure Card (IKA) to section Inalum Internal Control (IIC). The application of Inalum Secure Card (IKA) have not given rewards and sanctions to the workers. Based on the results of the study, PT.Inalum Kuala Tanjung is expected to improve communication about Occupational Health and Safety (OHS), especially regarding the behavior-based safety program so that the workers could care and aware to behave a safety work to create Occupational Safety and Health (OHS) culture.